2016
DOI: 10.1186/s12889-016-3867-2
|View full text |Cite
|
Sign up to set email alerts
|

The response to receiving phenotypic and genetic coronary heart disease risk scores and lifestyle advice – a qualitative study

Abstract: BackgroundIndividuals routinely receive information about their risk of coronary heart disease (CHD) based on traditional risk factors as part of their primary care. We are also able to calculate individual’s risk of CHD based on their genetic information and at present genetic testing for common diseases is available to the public. Due to the limitations in previous studies further understanding is needed about the impact of the risk information on individual’s well-being and health-behaviour. We aimed to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Face-to-face interviews with a purposive sample of 41 participants were conducted as part of the INFORM trial by an experienced qualitative researcher (GS). Full details of the recruitment and methods are reported in detail elsewhere [ 23 ]. Briefly, in order to sample participants who could provide the richest data on the primary trial question, participants who received medium to high risk scores (a 10-year CHD risk >10% or heart age at least two years older than their real age) were mainly selected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Face-to-face interviews with a purposive sample of 41 participants were conducted as part of the INFORM trial by an experienced qualitative researcher (GS). Full details of the recruitment and methods are reported in detail elsewhere [ 23 ]. Briefly, in order to sample participants who could provide the richest data on the primary trial question, participants who received medium to high risk scores (a 10-year CHD risk >10% or heart age at least two years older than their real age) were mainly selected.…”
Section: Methodsmentioning
confidence: 99%
“…The Information and Risk Modification (INFORM) Trial [ 22 ] was a randomized controlled trial comparing the impact of providing phenotypic and genetic CHD risk scores alongside a Web-based lifestyle intervention. In additional to behavioral outcomes, INFORM included quantitative measurements of engagement with the Web-based lifestyle intervention and a nested qualitative study with face-to-face individual interviews with participants throughout the trial [ 23 ]. The aims of this study were to use the data from the face-to-face interviews to explore the factors associated with different levels of engagement with the Web-based intervention, and the barriers and facilitators to engagement in general.…”
Section: Introductionmentioning
confidence: 99%
“…It should rather be considered an incentive to address the question from a different perspective. The above-mentioned qualitative study3 revealed that the calculated risk scores provided as percentages to the INFORM participants were usually lower than expected, rarely perceived as meaningful—especially genetic risk scores—and mostly overlooked. Genetic scores may even elicit fatalistic attitudes with a risk perceived as unmodifiable, thus suggesting that lifestyle changes would be pain without gain.…”
mentioning
confidence: 93%
“…In fact, the lack of difference before and after information within each group might hide diverging trends according to the interplay of expected risk, actual risk and individual psychological vulnerability. Indeed, a qualitative analysis3 highlighted how variable was the psychological response of INFORM participants to the information they were provided with.…”
mentioning
confidence: 99%
See 1 more Smart Citation